APOE Is Associated With Serum Tau Following Uncomplicated Mild Traumatic Brain Injury - Lippa, Sara M.; Lange, Rael T.; Dalgard, Clifton L.; Soltis, Anthony R.; Guedes, Vivian A.; Brickell, Tracey A.; French, Louis M.; Gill, Jessica (Frontiers in Neurology, 2022)
Background and Objectives APOE e4 has been linked to poor outcome following traumatic brain injury (TBI); however, the mechanisms behind this relationship are unclear. Few studies have investigated the relationship between the APOE genotype and established brain related protein biomarkers following TBI. The purpose of this study was to examine this relationship in service members and veterans (SMVs) following TBI. Methods Participants were 209 SMVs [124 uncomplicated mild TBI (mTBI); 85 complicated mild, moderate, severe, or penetrating TBI (mod-sev TBI)] prospectively enrolled in the DVBIC-TBICoE 15-Year Longitudinal TBI Study. APOE genotyping was undertaken using non-fasting blood serum samples. Participants were divided into three groups: APOE e2+, APOE e3/e3, and APOE e4+. Results In participants with mTBI, those with the APOE e2 allele had significantly lower levels of tau than those with APOE e4 (p = 0.005, r = 0.43, medium-large effect size). Those with APOE e3/e3 trended toward having higher tau than those APOE e2+ (p = 0.076, r = 0.20, small-medium effect size) and lower tau than those with APOE e4+ (p = 0.062, r = 0.21, small-medium effect size). There were no significant differences in biomarkers based on APOE in the mod-sev TBI group. Discussion This study is the first to demonstrate APOE genotype is related to serum tau levels following a mTBI, extending prior findings to human serum following mTBI. In addition to higher serum tau levels in APOE e4 carriers, lower tau levels were observed in APOE e2 carriers, suggesting a possible protective effect.